Protection of springs in forest areas - Satriawan, Hera Alvina; S, Nathania Permata (Priviet Social Sciences Journal, 2025)
Spring water is an essential natural resource that supports ecological stability and human survival, making its protection a significant environmental and legal governance issue. Amid increasing water demand, climate variability, and forest degradation, the State is required to establish a regulatory framework to preserve spring water, particularly in protected forest areas. This study examines the legal regulations governing the protection of spring water in forest zones using a normative legal research method. This study adopts a statutory approach by reviewing the 1945 Constitution, the Water Resources Act, the Forestry Act, and the Environmental Protection and Management Act, as well as a conceptual approach to analyze the doctrines of state control, the ecological function of forests, and principles of environmental protection. The findings demonstrate that protecting spring water is a constitutional mandate reinforced by interrelated sectoral statutes. Forests perform a critical hydrological function; thus, the degradation of forest areas directly affects the quality and availability of water. The Environmental Protection Act provides preventive legal instruments, such as the Strategic Environmental Assessment, Environmental Impact Assessment, and environmental approval, to control harmful activities. Additionally, forest rehabilitation programs and the designation of protected local zones strengthen the conservation measures. Although the legal framework is comprehensive, its effectiveness is hindered by policy inconsistencies, weak supervision, and conflicts of interest in land use decisions. An integrated, multilayered statutory system regulates the legal protection of spring water in forested areas. However, its success depends on consistent law enforcement, intergovernmental coordination, and strengthened local regulations to ensure sustainable water availability for future generations of farmers.